Analytical comparison on two incentive policies for shore power equipped ships in berthing activities. (May 2022) - Zhen, Lu; Wang, Wencheng; Lin, Shumin
Abstract: Exhaust fumes from the shipping industry pose a serious threat to the environment and residents' health in coastal areas. The use of shore power during ship berthing is an effective measure to reduce air pollution near the port. Due to the high investment cost, the deployment of the ship-borne power receiving system is seriously hindered. This study analyzes the impact of government-subsidy-based incentive policy and berthing-priority-based incentive policy on ship-borne power receiving system deployment. The two incentive policies are compared in a quantitative way. A nonlinear programming model is constructed to optimize the ship-borne power receiving system deployment, berth allocation, and the order of ships being served in each berth. Due to the complexity of the proposed model, a sequential heuristic algorithm is designed. A critical-shaking neighborhood search method is applied to improve the solution quality of the sequential heuristic algorithm. In extensive numerical experiments, the effectiveness and efficiency of the improved algorithm are verified by comparing it with particle swarm optimization algorithm, tabu search algorithm, and a lower bound of the proposed model. Experimental results show that the berthing-priority-based incentive policy is recommended to be implemented when the government subsidy rate is low. Based on the experimental results, some management implications are outlined. Highlights: Develop a model to optimize the ship-borne power receiving system deployment. Analyze the impact of two incentive policies on ship-borne power receiving system deployment. Verify the effectiveness of the improved sequential heuristic algorithm by a lower bound of the model. Management implications may promote the application of ship-borne power receiving systems.